Economic insecurity in the 2022 Italian general election: mobilization or withdrawal? - Giacomo Salvarani; Fabio Bordignon; Luigi Ceccarini (QOE-IJES)
A right-wing coalition led by Giorgia Meloni’s Brothers of Italy (FdI) emerged as the clear winner of the 2022 Italian general election, with voter turnout reaching its lowest level in the history of the Italian Republic. This result unfolded amidst a long-standing sense of economic stagnation, escalating inequality, and rising inflation. The article explores the relationship between individual economic insecurity and the 2022 election results. There is an assumption in both public and scholarly discourse that economic insecurity is responsible for the rise of populist and, particularly, populist radical-right (PRR) parties. Does the 2022 Italian general election represent a case of mobilization or withdrawal of the economically insecure electorate? Building on the literature on populist success and the economy’s effects on political behavior, we find that economic insecurity was not behind the success of the PRR parties (the League and FdI) in the 2022 election. It was also not associated with the vote for the main populist non-radical-right party in the Italian political landscape: the 5-Star Movement. On the contrary, in this election, economic insecurity mostly deterred voters from casting their ballots, and the success of the PRR can mostly be explained by anti-immigration attitudes.